2018
DOI: 10.24193/tras.54e.4
|View full text |Cite
|
Sign up to set email alerts
|

Preferences of Poles concerning the Shape of Regional Policy and the Allocation of European Funds

Abstract: The social reception of economic development processes has been underrated in studies conducted so far. The scarcity of such analyses may be perceived as a problem especially in the case of CEE states, in which economic growth has often been accompanied by a deepening of the socio-economic inequalities in the recent years. This article aims to identify the preferences of Poles concerning the goals of regional policy and the assignment of the European funds. Special attention was given to the differences among … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 18 publications
0
3
0
Order By: Relevance
“…When outcomes are evaluated, it is debatable if they are really relevant for local economic development or quality of life [11]. This situation is not unique to Romania and it can be encounter in other former communist countries experiencing significant territorial disparities [12,13]. Moreover, there seems to be little distinction between the objectives followed by these programs-economic development and poverty reduction are very often lumped together with improvements in quality of life, depending on which data is available post-implementation.…”
Section: Introductionmentioning
confidence: 99%
“…When outcomes are evaluated, it is debatable if they are really relevant for local economic development or quality of life [11]. This situation is not unique to Romania and it can be encounter in other former communist countries experiencing significant territorial disparities [12,13]. Moreover, there seems to be little distinction between the objectives followed by these programs-economic development and poverty reduction are very often lumped together with improvements in quality of life, depending on which data is available post-implementation.…”
Section: Introductionmentioning
confidence: 99%
“…This can be assessed for instance by the opinion of stakeholders on which kinds of projects should be granted. It was identified that while Polish public authorities are more concentrate on "hard" projects considering mainly infrastructure, citizens are willing to invest in both "hard" as well as "soft" projects influencing social aspects of RES implementation [69]. Therefore, in the process of strategies and planning the final allocation can vary depending on the impact of each stakeholder group.…”
Section: Discussionmentioning
confidence: 99%
“…In European conditions socio-economic transformation is strongly related to the support of European Funds [14]. One of the major aspects of this transformation is the implementation of RES and in that way shift into low-carbon economy [15].…”
Section: Introductionmentioning
confidence: 99%